Entrepreneurial Orientation and Personal Growth on Organizational Performance: The Role of Innovation Capability - Ainunnisa Al Rumra; Bima Cinintya Pratama; Eko Hariyanto; Hardiyanto Wibowo (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
Organizational performance is the success of an organization in achieving competitive advantage that is influenced by entrepreneurial attitude, mindset, personal growth, and innovation ability. This research aimsto examine how the entrepreneurial attitude, mindset, and personal growth adopted by companies affect company performance through the innovation process. The population in this study is 19,044 MSMEs in Banyumas, Cilacap, and Brebes regencies. Sampling was carried out by stratified sampling method so that a sample of 200 respondents was obtained. This research uses the SMART – PLS analysis method. The results showed that entrepreneurial attitude, mindset, personal growth, and innovation ability positively affect organizational performance, and innovation ability mediates entrepreneurial attitude, mindset , personal growth towards performance organization.